Hybrid Entropy Decomposition And Support Vector Machine Method For Image Classification For Crop Fields - Tan, Chue Poh (2007)
In this thesis, a Synthetic Aperture Radar (SAR) image classifier based on the "Entropy Decomposition and Support Vector Machine" (EDSVM) is developed for classification of crop fields. The key parameters extracted from Entropy Decomposition (ED) are applied to Support Vector Machine (SVM) classifier and it performs efficient image classifications.